Let There Be Light—Digital Eye Strain (DES) in Children as a Shadow Pandemic in the Era of COVID-19: A Mini Review - Bhattacharya, Sudip; Heidler, Petra; Saleem, Sheikh Mohd; Marzo, Roy Rillera (Frontiers in Public Health, 2022)
COVID-19 pandemic, which is often ignored by the public. Aim-The current paper is aimed at discussing the ill effect of digital screens on eyes in the wake of COVID-19 pandemic. Methodology-A literature search was done using “PubMed,” “Google scholar” and “Scopus” using key terms like “Digital Eye Strain”, “Eyestrain” or “Computer Vision Syndrome.” Relevant articles were identified and included to support the argument for this narrative review. Results-Studies conducted in UK reported that 68% of children extensively use computers while 54% undertake online activities by reaching 3 years of their age. Similar studies estimated 4 hours and 45 minutes per day screen exposure time among adults in the UK. Indian studies reveal that the prevalence of DES is 69% and 50% respectively. Indian ophthalmologists found that computer-using and specialized ophthalmologists were more informed of symptoms and diagnostic signs but were misinformed about treatment modalities. The use of social media and multitasking is particularly prominent among younger adults with 87% of individuals aged 20–29 years reporting the use of two or more digital devices simultaneously. It has been observed that the use of computer glasses corrects refractive errors and helps in the reduction of symptoms, while precision spectral filters help in reducing symptoms of micro-fluctuation of accommodation. Conclusion-We concluded that DES is emerging globally as “Shadow Pandemic” and its high time to respond, especially by the community ophthalmologists, the public health, and educational sectors to prevent this.